Seleção de progênies de Myracrodruon urundeuva baseada em caracteres fenológicos e de crescimento para reconstituição de áreas de Reserva Legal - Bertonha, Laerte João [UNESP]; Freitas, Miguel Luiz Menezes; Cambuim, José; De Moraes, Mario Luiz Teixeira [UNESP]; Sebbenn, Alexandre Magno (Instituto de Pesquisa e Estudos Florestais (IPEF), 2016)
Reforestation of legal reserve areas with native tree species is a way to follow legal requirements. This activity can be combined with the use of genetically improved species, increasing the sustainable use of the farm and, consequently, encouraging rural landowners to recovery such areas. This paper discusses the use of Myracrodruon urundeuva in the recovery of degraded areas, with guidelines on how to obtain seeds with a certain genetic improvement. The aim is to turn two progeny tests established in two planting systems, into seedling seed orchards. Therefore, we evaluated the sex ratio, genetic variation of traits diameter at breast height (DBH), total height (TH), height of canopy insertion (IC), canopy height (HC), mean canopy diameter (ACD), canopy volume (CV) and the production of diaspores in two progeny tests with 16.5 years-old, installed in Selvíria (MS). In both planting systems, the sex ratio of males and females was approximately of 5:1. In both planting systems the best 45 male plants and the best nine female plants were selected for DBH, resulting in a genetic gain of 11.1% in the homogenous planting system and 24.3% in the intercalated planting system. The results validate the proposed improvement of this species and any of the selected planting system can be successfully used in the production of seeds for reforestation of a legal reserve. The method can also be adapted to other species.
Selection of myracrodruon urundeuva progenies based on phenological traits and growth for reconstitution of legal reserve areas
Keywords: Ex situ genetic conservation; Legal reserve; Sustainable use